Abu ibeji’s salafi movement and the muslim ummah in Ibadan (2016)
Salafi movement developed in the second half the eighteenth century with the aim of redirecting Muslims to pristine Islam. However, some radical variants of Salafi movement which re-interpret Islamic religious teachings and constitute a challenge to other Muslims have emerged. Although scholars have focused on deviant Muslim groups, little has been done in the area of studying the composition and the ideological base of the Ibadan-based Abu Ibeji group; hence, the paper fills the gap by examining the ideological base of this radical Muslim group, as against established extant Islamic teachings, and their implications for other Muslims. The paper adopts content analysis approach and descriptive survey design. It analyses Islamic religious texts and ideas gleaned from in-depth interviews with selected members of the religious group, as well as the leadership of the Muslim community. Abu Ibeji group has recorded noticeable changes in established Islamic religious practices and principles such as prayer timing, gender rights, getting formal education, greetings and child naming ceremony among others. The group is not only overzealous but also plagued with incompetent leaders, ignorant followers and poverty. The group has the potential of developing into a terrorist organisation if something is not urgently done to curb it. There is the need for the Muslim community in Ibadan, in conjunction with the League of Imams and Alfas, to embark on an intensive reorientation and empowerment of the group members and, by extension, the general public.